Spremembe vodne bilance v Sloveniji v obdobju 1961–2024 - Žiberna, Igor (Časopis za zgodovino in narodopisje, 2024)
This article presents an analysis of the status and trends related to the meteorological (climatological) water balance, focusing on the differences between precipitation and evapotranspiration. It examines trends in precipitation, potential evapotranspiration, and water balance across twelve meteorological stations in Slovenia from 1961 to 2023. The article outlines both the causes and consequences of these observed trends. Additionally, it explores the spatial distribution characteristics of the water balance in Slovenia, utilizing georeferenced raster data from the Chelsa Climate database for the period of 1981 to 2010.
Keywords: climate change; drought; podnebne spremembe; Slovenia; Slovenija; suša; vodna bilanca; water balance